POTENSI PENGEMBANGAN BUDIDAYA IKAN DALAM KERAMBA DI PERAIRAN UMUM KABUPATEN SIAK - Rusliadi ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2009)
Siak Regency has a public waters such as rivers, swamps and lakes / seaample. Utilization is still limited as the fishing, although production is very low.Meanwhile, public waters are particularly Mandau River and Gasib River has thepotential for development of aquaculture, especially fish culture in cages. Thispotential can be seen from the area, physical condition, chemical and biologicalwater.